Azimuth stern drive (ASD) vector tugs positioning and towing force prediction during docking, steering and braking maneuvers. (May 2021) - Barrera, R.D.; Schiaveto Neto, L.A.; Vieira, D.P.; Mesquita, E.S.; Tannuri, E.A.
Abstract: Ship Maneuvering Simulators have proved to be powerful tools for analyzing the feasibility of docking, steering, and braking maneuvers under the assistance of tugboats. To represent tugboats' actuation, the so-called "vector tug" model is normally applied. This model is usually represented as simplified external forces, causing a significant loss of realism concerning the tugboat's towing force and its actuating position. The main objective of this work is to provide an innovative approach for vector tug actuation modeling in such a way that both the towing forces and tugboat positions are correctly predicted during direct Push and Pull operation modes, which are usually performed under low speeds, during docking maneuvers. Besides, the steering and braking maneuvers will be addressed, with the corresponding predictions during the Indirect Pull operation, where the tugboat acts as an aerofoil, with the resultant lift force generated being transmitted across the tow line. In order to perform the predictions, the authors first used CFD methods to obtain the hydrodynamic coefficients for a harbour tugboat hull and an escort tugboat hull. Afterwards, they developed a Static Equilibrium Model combined with optimization techniques. The obtained results were validated against literature data and in the Numerical Offshore Tank Laboratory (TPN-USP) simulator.